Reliable DNA Markers for a Previously Unidentified, Yet Broadly Deployed Hessian Fly Resistance Gene on Chromosome 6B in Pacific Northwest Spring Wheat Varieties - Prather, Samuel; Schneider, Tavin; Gaham Godoy, Jayfred; Odubiyi, Steven; Bosque-Perez, Nilsa A.; Rashed, Arash; Rynearson, Sheri; Pumphrey, Michael O. (Frontiers in Plant Science, 2022)
Hessian fly [Mayetiola destructor (Say)] is a major pest of wheat (Triticum aestivum L.) throughout the USA and in several other countries. A highly effective and economically feasible way to control Hessian fly is with resistant cultivars. To date, over 37 Hessian fly resistance genes have been discovered and their approximate locations mapped. Resistance breeding is still limited, though, by the genes’ effectiveness against predominant Hessian fly biotypes in a given production area, genetic markers which are developed for low-throughput marker systems, poorly adapted donor germplasm, and/or the inadequacy of closely-linked DNA markers to track effective resistance genes in diverse genetic backgrounds. The purposes of this study were to determine the location of the Hessian fly resistance gene in the cultivar ‘Kelse’ (PI 653842) and to develop and validate Kompetitive Allele Specific PCR (KASP) markers for the resistance locus. A mapping population was genotyped and screened for Hessian fly resistance. The resulting linkage map created from 2089 Single Nucleotide Polymorphism SNP markers placed the resistance locus on the chromosome 6B short arm, near where H34 has been reported. Three flanking SNPs near the resistance locus were converted to KASP assays which were then validated by fine-mapping and testing a large panel of breeding lines from hard and soft wheat germplasm adapted to the Pacific Northwest (PNW). The KASP markers presented here are tightly linked to the resistance locus and can be used for marker-assisted selection (MAS) by breeders working on Hessian fly resistance and allow confirmation of this Hessian fly resistance gene in diverse germplasm.